Linchamentos e a sede de justiça popular: análise dos casos ocorridos entre 2014 a 2017 no estado do Amazonas - Lima, Suzane Oliveira Da Cunha (2017)
In current days, we are hit with news of common lynchings across the country. A group of people who legitimize their conception of justice in an individual, who does not know whether or not he has committed a crime, but in truth, for lynchers no matter the guilt, the important thing is to quench the if you do "justice" on time, at any cost. Thus one realizes that man can be as primitive as one day history tells us, returning to medieval times in a matter of seconds, evidencing the conflicts of modern man. The research aimed to demonstrate how close we are to medieval barbarism that we believe we have overcome. 153 cases of lynching were mapped in Amazonas, and it was observed that in all cases the ideal victim profile is the man under 30 years of age and who has committed crimes against the patrimony and sexual violence. Through the survey of the occurrences of lynchings occurring in the Capital and in the interior, it is clear that this is a frequent practice, showing some acceptance before the population, which appears to be part of a social group that does not share the same values of state justice, opting for to perform rituals that satisfy the immediate need to perform a kind of social hygiene, and consequently to stop the escalation of violence. On the other hand, it also demonstrates the legitimacy crisis of state-administered justice, whose values differ from those who practice lynching, also showing a certain negligence in ascertaining these cases.